Discrete pore and particle size distributions during pore blocking and cake filtration (Research, Society and Development, 2024)
Modeling membrane filtration is important for plenty industrial applications. The understanding of the phenomena and related mechanisms aims at the improvement of techniques in different areas. Therefore, different authors have proposed models to describe the mechanisms related to the filtration process involving either cake build-up or blocking processes, a few of them however have proposed both concepts simultaneously, although none considered pore and particle size distribution during the process, which is the proposal brought up in this paper. Transient solutions for filtrate volume and filter cake thickness as a function of initial pore and particle size distributions are obtained. Good matching between the studied experimental data and the proposed model was observed. In general, the results showed that permeability reduction and filtrate volume are strongly influenced by the initial pore and particle size distributions. In addition, the cake build-up rate depends on both the particle size distribution and the residual flow through blocked pores. It was observed that, after all the largest particles have blocked the smaller pores, effective permeability and flow rate vary only due to cake build-up. Finally, because the proposed empirical parameters do not depend on the pore size distribution, this model can be applied for predicting permeability decline for any feed concentration.